Les intérêts diffus, instruments pour la justice et la démocratie environnementale - Alexandra Aragão (VertigO, 2015)
The legal concept of diffuse interests is an instrument for environmental justice and democracy. This is a consequence of the role of diffuse interests in the context of the judicial process and its social functions. In some legal systems, there is a recognition of a third category of interests, beyond the individual interests and the public interest. It is the trans-individual interests. The diffuse interests are a subcategory of trans-individual interests. The system of actio popularis is the culmination of the diffuse interests’ protection goal. The result is a more effective protection of environmental rights through broad judicial standing.